Kritik Fenomena Perilaku Phubbing sebagai Perusak Hubungan Sosial: Studi Takhrij dan Syarah Hadis - Ahmad Mustolah; Hidayatul Fikra; Saifudin Nur (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to examine the hadith about the phenomenon of phubbing in the social environment. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods through contemporary analysis. The result of this research is the quality of the hadith about phubbing the history of Imam Ahmad No. 2808 is valid. The discussion of this research reveals that in the hadith the Prophet Muhammad Saw. implicitly set an example so that Muslims always maintain relationships with other people, especially in face-to-face meetings so as not to drown in the phubbing phenomenon. This study concludes that the phenomenon of phubbing is something that should be avoided by anyone, so that communication and relationships between people are maintained properly. This study recommends further research on the harmony of the hadith narrated by Imam Ahmad No. 2808 with the hadith an-Nasa'i No. 5194 regarding the phubbing phenomenon with a different approach.